Analysis and Design of Irrigation Pumps Using Hybrid Solar-Grid Energy with Arduino Uno Control - Mangera, Paulus; Cipto, Cipto (ELKHA : Jurnal Teknik Elektro, 2025)
The need for a reliable water supply system and encourages the development of renewable energy technology based on solar power. This study designs and builds a hybrid solar-grid energy system to operate a 12V submersible pump based on an Arduino Uno microcontroller that combines a 200 Wp solar panel energy source and a grid electricity source, with a PWM charge controller and energy storage using a 12V 70Ah lead-acid battery. The 125W submersible pump is the main load for water distribution. Photovoltaic Power Output (PVOUT) map data, Merauke Region has an average annual solar energy potential of 1600"“1800 kWh/kWp, indicating high feasibility for implementing a solar power system. Arduino Uno is used to control the automatic switching system between solar energy and the grid based on the battery voltage level. The test results show that the system is able to operate the pump effectively in sunny conditions without full dependence on the grid, and can switch automatically when the energy from the solar panel is insufficient. The amount of energy coming from the 200 WP solar cell (Pin) is 952.03 W, the amount of energy released by the 200 WP solar cell (Pout) is 145.20 W, with a solar panel efficiency of 15.2%, the average radiation intensity during testing is 732.33 W/m ² with a maximum temperature of 31 °C.